Intestinal Atresia Occurring in Association with Placental Fetal Thrombotic Vasculopathy: A Case Report with Literature Review. (January 2013) - Lian, Derrick W.Q.; Lam, Joyce C.M.; Aung, Aye Chan Lwin; Li, Faye X.; Chang, Kenneth T.E.
Fetal thrombotic vasculopathy (FTV) is a thrombo-occlusive disorder of the placenta that has been reported in association with perinatal conditions such as cardiac abnormalities, neurological injury, and perinatal liver disease. These complications are related to fetal circulation vascular compromise. We herein report a previously undocumented association of congenital intestinal atresia and placental FTV. Vascular occlusion of the fetal mesenteric vessels has been hypothesized to result in congenital intestinal atresia. Our report provides support for this vascular hypothesis and illustrates the value of formal pathological examination of the placenta in explaining this occurrence of congenital intestinal atresia.